Plan and Evaluation of the Development Project - Pěkný, Ondřej; Synek, Miloslav, 1935-2022; Bydžovský, Matěj; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2009)
The aim of the thesis is to explain main aspects of the development and elaboration of a real project of mountain apartments on the level of a feasibility study. The thesis is divided up into two parts. Theoretical part describes individual stages of the development, involved entities and the procedure of obtaining building permit, which is all necessary for the implementation of the project. The emphasis is laid on funding, namely financial resources and tax optimalization. The second part deals with the develoment project itsef, which is the construction of weekend apartments in the mountains. The project aims at finding the right use of a specific piece of land, the concept of construction and its funding. Further on the thesis contains sensibility analysis, market and competion analysis and SWOT analysis and identification of main risks including their solution and possible preventive measures. The final part of the thesis focuses on evaluation of this project and its comparison with several competitive projects.
Vedoucí práce: Miloslav Synek
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2010
Rok obhajoby 2010
Keywords: podniková ekonomika a management [obor dipl. práce]; diplomové práce; master's theses